2006
DOI: 10.1002/chin.200609202
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for β‐Selenoglycoside Synthesis Using β‐p‐Methylbenzoyl Selenoglycoside as the Selenating Unit.

Abstract: Carbohydrates U 0500A Facile Method for β-Selenoglycoside Synthesis Using β-p-Methylbenzoyl Selenoglycoside as the Selenating Unit. -Acylseleno glycosides (I) and (VI) are activated by the action of a secondary amine and Cs2CO3 to produce an anomeric selenolate anion, which reacts in situ with various electrophiles. Novel selenoglycosides including selenooligosaccharides and selenoglycosylamine are obtained with retention of anomeric stereochemistry. -(KAWAI, Y.; ANDO, H.; OZEKI, H.; KOKETSU, M.; ISHIHARA*, H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…BMD (Figure ) was prepared and characterized in our laboratory by the method previously described Kawai et al . Analysis of the 1 H NMR and 13 C NMR spectra showed analytical and spectroscopic data in full agreement with their assigned structures.…”
Section: Methodsmentioning
confidence: 88%
“…BMD (Figure ) was prepared and characterized in our laboratory by the method previously described Kawai et al . Analysis of the 1 H NMR and 13 C NMR spectra showed analytical and spectroscopic data in full agreement with their assigned structures.…”
Section: Methodsmentioning
confidence: 88%
“…The above results revealed that the yields of the product dropped with the decrease in basicity. Further, these findings suggested that acyl thioglycoside is effectively activated by using 1.5 equiv of Cs 2 CO 3 and readily produces the thiolate anion in situ (according to the methods of Ando and Ishihira 23 ), which completely converted under optimized reaction conditions to thioglycoside 4a in 97% yield (entry 2). With these encouraging results, we endeavor to afford Seglycoside 5a by employing galactosylselenoacetate 3a, coupled with p-QM 1a under the same optimized conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%